The socio-economic approach to the study of modern economic systems. Post-capitalism. Part 2 = Społeczno-ekonomiczne podejście do badań współczesnych systemów gospodarczych. Postkapitalizm. Część 2 - Akulich, Maria; Kaźmierczyk, Jerzy (Zielona Góra: Faculty of Economics and Management Press)
This article examines modern economy and society taking the formational approach, which is based on the concept that for the modern world and the predicted future, the economy will remain the foundation of society. An understanding of modern society as a post-capitalist society is proposed and justified.
Keywords: socjalizm; kapitalizm; post-kapitalizm; globalizacja; system gospodarczy; społeczeństwo postkapitalistyczne; socialism; capitalism; post-capitalism; globalization; economic systems; post-capitalist society